Decision quality value creation from better business decisions - Spetzler, Carl S.; Winter, Hannah; Meyer, Jennifer (Hoboken, New Jersey Wiley, 2016)
"Add value with every decision using a simple yet powerful framework Few things are as valuable in business, and in life, as the ability to make good decisions. Can you imagine how much more rewarding your life and your business would be if every decision you made were the best it could be? Decision Quality empowers you to make the best possible choice and get more of what you truly want from every decision. Dr. Carl Spetzler is a leader in the field of decision science and has worked with organizations across industries to improve their decision-making capabilities. He and his co-authors, all experienced consultants and educators in this field, show you how to frame a problem or opportunity, create a set of attractive alternatives, identify relevant uncertain information, clarify the values that are important in the decision, apply tools of analysis, and develop buy-in among stakeholders. Their straightforward approach is elegantly simple, yet practical and powerful. It can be applied to all types of decisions. Our business and our personal lives are marked by a stream of decisions. Some are small. Some are large. Some are life-altering or strategic. How well we make those decisions truly matters. This book gives you a framework and thinking tools that will help you to improve the odds of getting more of what you value from every choice. You will learn: The six element of decisions quality, and how to apply them The difference between a good decision and a good outcome Why a decision can only be as good as the best of the available alternative Methods for making both 'significant' and strategic decisions The mental traps that undermine decision quality and how to avoid them How to deal with uncertainty--a factor in every important choice How to judge the quality of a decision at the time you're making it How organizations have benefited from building quality into their decisions. Many people are satisfied with 'good enough' when making important decisions. This book provides a method that will take you and your co-workers beyond 'good enough' to true Decision Quality"--Publisher.
"Aimed at executive and management-level decision makers in every industry, Decision Quality: Value Creation from Better Business Decisions provides a proven and real-world-tested framework for improving business decision quality"--Publisher.
Includes bibliographical references and index.
Keywords: Decision making